2005
DOI: 10.1093/jn/135.3.598
|View full text |Cite
|
Sign up to set email alerts
|

Lignans Are Involved in the Antitumor Activity of Wheat Bran in Colon Cancer SW480 Cells,

Abstract: Wheat bran was shown to provide protection against colorectal cancer in human intervention and animal studies. Our recent study showed, however, that antitumor activities of wheat bran from various wheat cultivars differed significantly even when wheat fiber was equal in diets. We hypothesized that phytochemical lignans in wheat bran may account for the differences among wheat cultivars in cancer prevention. The concentration of a major lignan, secoisolariciresinol diglycoside, was determined by HPLC in 4 sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 139 publications
(98 citation statements)
references
References 39 publications
0
96
0
2
Order By: Relevance
“…We also found that dietary SDG at 46 0.01% significantly reduced azoxymethane-induced formation of aberrant crypt foci in F344 rats 47 [10]. In addition, we have shown that enterolactone and enterodiol or both in combinations 48 inhibit human cancer cell growth through inducing S-phase cell cycle arrest and apoptosis [9]. 49…”
Section: Introduction 36mentioning
confidence: 77%
See 4 more Smart Citations
“…We also found that dietary SDG at 46 0.01% significantly reduced azoxymethane-induced formation of aberrant crypt foci in F344 rats 47 [10]. In addition, we have shown that enterolactone and enterodiol or both in combinations 48 inhibit human cancer cell growth through inducing S-phase cell cycle arrest and apoptosis [9]. 49…”
Section: Introduction 36mentioning
confidence: 77%
“…43 Many studies show that SDG has cancer preventive properties in animal models. Our 44 previous study demonstrated that SDG levels in wheat bran from various wheat cultivars were 45 correlated to antitumor activities in APC-Min mice [9]. We also found that dietary SDG at 46 0.01% significantly reduced azoxymethane-induced formation of aberrant crypt foci in F344 rats 47 [10].…”
Section: Introduction 36mentioning
confidence: 77%
See 3 more Smart Citations